FORMULATION AND EVALUATION OF PEEL-OFF GEL MASK FROM EXTRACT OF RED SPINACH (Amaranthus tricolor L.) - Nur Saadah Daud; Ade Ainun Insani; Eny Nurhikma (Jurnal Farmasi Sains dan Praktis, 2021)
Red spinach (Amaranthus tricolor L.) contains various secondary metabolites that act as antioxidants. These activities can be used to maintain the health of facial skin due to the negative impact of free radicals in the form of cosmetic preparations of peel-off gel mask. This study aims to make a peel-off gel mask preparation from red spinach extract that meets the requirements for physical evaluation of the preparation. The extraction process was carried out by maceration method using 96% ethanol as solvent. The thick extract was then made into a peel-off gel mask preparation with variations in extract concentration of 0.5% (F1), 1% (F2), and 2% (F3). Furthermore, physical evaluation of the preparation at room temperature for 4 weeks of storage, drying time test, irritation test, preference test, and cycling test was carried out. The red spinach used has been determined as Amaranthus tricolor L. The results of phytochemical screening of the thick extract showed that the extract contained positive alkaloids, saponins and flavonoids. The results of the evaluation showed that all preparations met the physical evaluation requirements and were not irritating. The higher the concentration of the extract, the darker the color of the preparation and the higher the pH and viscosity values. The preparation was stable during storage at room temperature but decreased in pH value and dispersion after passing 6 cycles of cycling test. The results of the preference test showed 60% of respondents liked F3, which is a formula with a dark green color, a distinctive aroma of red spinach, homogeneous, pH 7.54, dispersion of 6.2 cm, the viscosity of 7200 cps and drying time of 20.23 minutes.